2017
DOI: 10.1080/02656736.2017.1387941
|View full text |Cite
|
Sign up to set email alerts
|

Combined radiofrequency ablation and ethanol injection versus repeat hepatectomy for elderly patients with recurrent hepatocellular carcinoma after initial hepatic surgery

Abstract: RFA-PEI provides comparable OS and RFS to repeat hepatectomy for elderly patients with small recurrent HCC after hepatectomy but with fewer non-tumour-related deaths, major complications and shorter hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…In addition, TACE can also diminish the dissemination of HCC [29]. The combination of RFA and ethanol injection can also improve the efficiency of RFA and achieve comparable prognosis to hepatectomy for patients with small recurrent HCC [30]. Both MVI and early recurrence are adverse prognostic factors for HCC [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TACE can also diminish the dissemination of HCC [29]. The combination of RFA and ethanol injection can also improve the efficiency of RFA and achieve comparable prognosis to hepatectomy for patients with small recurrent HCC [30]. Both MVI and early recurrence are adverse prognostic factors for HCC [16].…”
Section: Discussionmentioning
confidence: 99%
“…reported that the prognoses of recurrent HCC patients who underwent salvage transplantation and repeated hepatectomy were similar, while the prognosis of patients who underwent repeated RFA was worst among the three therapies, although the backgrounds of patients differed among the treatment approaches. Chen et al . reported that RFA and percutaneous ethanol injection therapy provided comparable overall and recurrence‐free survival rates to repeated hepatectomy for elderly patients (≥70 years of age) with small recurrent HCC after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Достоверного различия в уровнях общей и безрецидивной выживаемости в двух группах выявлено не было. Вместе с тем, частота осложнений и длительность пребывания в стационаре больных, получивших малоинвазивное лечение (РЧА+ЧИЭ) были существенно ниже [19].…”
Section: би долгушин вю косыревunclassified